Recording culture : audio documentary and the ethnographic experience - Makagon, Daniel (SAGE, 2009)
Recording Culture holds up audio documentary as a premiere form of qualitative research which can serve as an inventive method of storytelling. Based in the practices of fieldwork, audio documentary increases the potential for researchers to reach academic and popular audiences and work collaboratively with people in the pursuit and representation of knowledge and experience. This volume not only explores the methodological issues related to audio documentary, it also provides readers with practical guidance on how to produce their own audio projects.This book is an ideal supplement for courses with titles such as Audio Documentary, Ethnography, Fieldwork, and Qualitative Methods. Instructors could easily use the text to guide students through the audio documentary process, enabling them to do ethnography using technology at a relatively lost cost.